Vecchiaia e vecchiezza: stile tardo di Toti Scialoja? - Di Nicola, Paolo (L’ospite ingrato, 2021)
Scialoja’s poetic production covers a thirty-year period, starting with the first nonsensical poems of the Seventies to the hexameters of the Nineties. Editorially, his production is divided in two main groups, on one side there are the “for children and nonsensical” poems, while on the other side there are the “ for adults and serious” poems. This paper aims to analize which are the clues of continuity and discontinuity in the second group, which includes poems written between 1979 and 1998. The topos of old age is used as a compass and it is expressed with two different words, vecchiaia and vecchiezza. Throught the reading of two poems, the first contained in Qui la vista è sui tigli, the second in Le costellazioni, the paper tries to outline a “late style” within the late production of Toti Scialoja.